Nano-silver modified carbon fiber coated organic silicon heat-conducting composite material as well as preparation method and application thereof

The treatment of oxidized asphalt-based carbon fibers through silane coupling agent and nanosilver modification will improve its dispersion and thermal conductivity in organic silicon, and solve the problem of difficult to take into account the thermal conductivity and mechanical properties of thermal interface materials, and realize the thermal conductivity coefficient and mechanics Performance improvement.

CN119286258APending Publication Date: 2025-01-10ZHENGZHOU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411402658.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing thermal conductivity and mechanical properties of existing thermally conductive interface materials are difficult to take into account in electronic devices, and the inorganic thermally conductive fillers have poor compatibility with polymer matrix, resulting in large interface thermal resistance and affecting heat dissipation performance.

Method used

The nano-silver modified carbon fiber is treated with oxidized asphalt-based carbon fibers to improve their dispersion and thermal conductivity in silicones, reduce the interface thermal resistance, and prepare nano-silver modified carbon fibers @ silicone thermally conductive composite materials.

Benefits of technology

The thermal conductivity is significantly improved at low filling amount, maintain good mechanical properties and thermal stability, and realize nano-silver modified carbon fiber@organosilicon thermally conductive composite material with low thermal filler filling amount, high thermal conductivity and excellent mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286258A_ABST
    Figure CN119286258A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of polymer-based heat-conducting interface materials, and particularly relates to a nano-silver modified carbon fiber coated organic silicon heat-conducting composite material as well as a preparation method and application thereof. The preparation method comprises the following steps: modifying oxidized pitch-based carbon fibers by using a silane coupling agent to obtain silane coupling agent modified carbon fibers, fixing nano-silver on the silane coupling agent modified carbon fibers to obtain nano-silver modified carbon fibers, and filling the nano-silver modified carbon fibers into organic silicon to obtain the nano-silver modified carbon fiber-organic silicon heat-conducting composite material. Under the low filling amount of the heat-conducting filler, the asphalt-based carbon fiber is modified by adopting the silane coupling agent and the nano-silver, so that the dispersity of the asphalt-based carbon fiber in organic silicon is improved, the heat-conducting property of the asphalt-based carbon fiber can be improved by fixing the nano-silver, the interface thermal resistance between the asphalt-based carbon fiber filler is reduced, and the thermal conductivity of the asphalt-based carbon fiber is improved. The heat-conducting property of the nano-silver modified carbon fiber coated organic silicon heat-conducting composite material is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polymer-based thermal conductive interface materials, and specifically relates to a nano-silver modified carbon fiber@organic silicon thermal conductive composite material and a preparation method and application thereof. Background Art

[0002] Electronic products are gradually developing towards integration, miniaturization and intelligence, which also makes the heat generated by electronic products more concentrated. Therefore, achieving efficient heat dissipation of chips to ensure the service life and product performance of electronic equipment or devices has become a key technical issue that needs to be solved urgently. Thermal interface materials can accelerate the heat dissipation process of radiators and are widely used in the field of electronic devices.

[0003] Thermal interface materials can fit well with chips and heat sinks respectively, and act as a bridge for heat transfer between chips and heat sinks. Therefore, thermal interface materials need to have good mechanical properties, flexibility and high thermal conductivity to meet the needs of chip heat dissipation. Traditional thermal interface materials are metal materials, such as gold, aluminum, silver, and copper, but these metal materials have the disadvantages of high specific gravity, difficult processing, and poor flexibility, which limits their widespread use in the field of electronic devices. Unlike metal materials, polymer materials have the characteristics of good flexibility, easy processing, low cost, and low specific gravity, which can meet the different usage scenarios and processing requirements of electronic devices. Therefore, polymer-based composite materials are widely used and studied.

[0004] However, pure polymers lack phonon transmission channels, and the thermal conductivity of polymers themselves is small, which cannot meet the use requirements of thermal conductive interfaces. It is usually necessary to add high thermal conductive fillers to polymers to improve the thermal conductivity of polymers. When the filling amount of high thermal conductive fillers is too low, the improvement of the thermal conductivity of polymer-based composites is not obvious; when the filling amount of thermal conductive fillers is too high, the mechanical properties of polymer-based composites are seriously affected, and too high a filling amount will greatly increase the interfacial thermal resistance between fillers, which will reduce the thermal conductivity of the interface material.

[0005] In addition, the existing technology improves the thermal conductivity of polymer-based composite materials by adding inorganic thermal conductive fillers such as diamond or boron nitride to the polymer, but these inorganic thermal conductive fillers usually have poor compatibility with the polymer matrix, and the interface thermal resistance between the filler and the matrix is ​​large, which is not conducive to heat transfer and heat dissipation of the thermal conductive interface material. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a nanosilver-modified carbon fiber @ silicone thermal conductive composite material and a preparation method and application thereof. The present invention first uses a silane coupling agent and nanosilver to modify the oxidized asphalt-based carbon fiber to obtain a nanosilver-modified carbon fiber, and then fills the nanosilver-modified carbon fiber into silicone to prepare a nanosilver-modified carbon fiber @ silicone thermal conductive composite material. In the nanosilver-modified carbon fiber @ silicone thermal conductive composite material obtained by the preparation method of the present invention, the modification of the silane coupling agent and nanosilver can improve the dispersibility of the asphalt-based carbon fiber in silicone, and the fixed nanosilver can also improve the thermal conductivity of the asphalt-based carbon fiber and reduce the interface thermal resistance between the asphalt-based carbon fiber fillers, thereby greatly improving the thermal conductivity of the nanosilver-modified carbon fiber @ silicone thermal conductive composite material, achieving a significant improvement in the thermal conductivity of the carbon fiber / silicon composite material under the premise of a low filling amount of the thermal conductive filler, and maintaining the good mechanical properties and thermal stability of the nanosilver-modified carbon fiber @ silicone thermal conductive composite material, and obtaining a nanosilver-modified carbon fiber @ silicone thermal conductive composite material with a low filling amount of the thermal conductive filler, a high thermal conductivity, good thermal stability, and excellent mechanical properties.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] The preparation method of nano silver modified carbon fiber@organic silicon thermal conductive composite material comprises the following steps:

[0009] The asphalt-based carbon fiber is subjected to oxidation treatment to increase the oxygen-containing functional groups on the surface of the asphalt-based carbon fiber to obtain oxidized asphalt-based carbon fiber.

[0010] The oxidized asphalt-based carbon fiber is modified with a silane coupling agent to obtain a silane coupling agent modified carbon fiber; the untreated asphalt-based carbon fiber has a relatively smooth surface, high inertness, low surface energy, few types and numbers of active functional groups, and poor interfacial bonding performance with silicone. Oxidation treatment is first performed and then surface modification is performed, which not only introduces active groups on the fiber surface through chemical reaction, thereby increasing the wettability and chemical bonding between the asphalt-based carbon fiber and silicone, but also increases the mechanical engagement between the asphalt-based carbon fiber and silicone by changing the surface morphology and roughness of the asphalt-based carbon fiber, thereby improving the interfacial bonding performance both chemically and physically, and effectively enhancing the performance of the nanosilver modified carbon fiber@silicon thermal conductive composite material.

[0011] The silane coupling agent modified carbon fiber is mixed with sodium citrate to obtain a silane coupling agent modified carbon fiber aqueous solution, the silane coupling agent modified carbon fiber aqueous solution, silver nitrate solution and sodium borohydride solution are mixed, and a silver ion reduction reaction is carried out, and then water is removed to obtain nanosilver modified carbon fiber, sodium citrate is used as a stabilizer to avoid nanosilver agglomeration, and the obtained nanosilver particles have a particle size between 100-500nm.

[0012] Vinyl silicone oil, hydrogen-containing silicone oil and Castel catalyst are mixed to obtain a mixture, nanosilver modified carbon fiber is added to the mixture, and the mixture is first homogenized and then vacuum cured. At this time, under the catalytic action of the catalyst, the vinyl silicone oil and the hydrogen-containing silicone oil undergo a silylation reaction, thereby cross-linking occurs to obtain a nanosilver modified carbon fiber@silicon thermal conductive composite material.

[0013] Preferably, the oxidation treatment method is: prepare a mixed acid solution containing sulfuric acid and nitric acid, place the asphalt-based carbon fiber in the mixed acid solution, perform oxidation reaction at 40-60° C. for 8-12 hours, and then wash with water until neutral.

[0014] Among them, the volume fraction of sulfuric acid is 98%, the volume fraction of nitric acid is 38%, and the volume ratio of sulfuric acid to nitric acid is 3-4:1.

[0015] Preferably, the mass ratio of the oxidized asphalt-based carbon fiber to the silane coupling agent is 8-10:0.1-0.5.

[0016] Preferably, the modification method is: mixing the oxidized asphalt-based carbon fiber and the silane coupling agent in an ethanol solution, and then reflux reacting at 60-80°C under normal pressure for 6-8h, wherein the ethanol solution is prepared in a ratio of 3-9:1 by volume of ethanol to deionized water.

[0017] Preferably, the mass ratio of silane coupling agent modified carbon fiber, sodium citrate, silver nitrate and sodium borohydride is 3-7g: 0.5-1.5g: 5.1-11.9mg: 3.192-3.99mg. The doping amount of nanosilver in the nanosilver modified carbon fiber @ organic silicon thermal conductive composite material is 1‰-5‰; too much silver nitrate cannot be completely reduced, and the nanosilver particles are too large after reduction, increasing the interface thermal resistance; too little silver nitrate, too little nanosilver is deposited on the surface of the asphalt-based carbon fiber, and a good thermal conductivity effect cannot be obtained.

[0018] Preferably, the method for the silver ion reduction reaction is: stirring the reaction at 40-60° C. for 2-4 hours.

[0019] Preferably, the mass ratio of vinyl silicone oil, hydrogen-containing silicone oil and Custer catalyst is 80-100:2-4:0.3-0.7.

[0020] Preferably, the mass ratio of the mixture to the nanosilver modified carbon fiber is 100:15-25. If the filling amount of the nanosilver modified carbon fiber is too little, the thermal conductivity of the nanosilver modified carbon fiber@silicone thermal conductive composite material will not be significantly improved; if the filling amount of the nanosilver modified carbon fiber is too much, the interface thermal resistance between the nanosilver modified carbon fiber fillers will increase sharply, which will reduce the thermal conductivity of the nanosilver modified carbon fiber@silicone thermal conductive composite material.

[0021] Preferably, the curing operation is: vacuum curing at 100-140° C. for 1-3 hours.

[0022] The present invention also protects the nanosilver modified carbon fiber @ silicone thermal conductive composite material obtained by the above preparation method. The diameter of the nanosilver modified carbon fiber is 3-10 μm and the length is 150-200 μm. If the size of the nanosilver modified carbon fiber is too large, the nanosilver modified carbon fiber @ silicone thermal conductive composite material cannot be cured or is difficult to cure, and is not conducive to improving the thermal conductivity of the nanosilver modified carbon fiber @ silicone thermal conductive composite material; if the size of the nanosilver modified carbon fiber is too small, it is not conducive to forming an effective heat conduction path between fillers, so the filler size needs to be within an appropriate range.

[0023] The present invention also protects the use of the above nano-silver modified carbon fiber@organic silicon thermal conductive composite material in the preparation of thermal conductive interface materials.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The present invention first uses a mixed acid solution to oxidize the asphalt-based carbon fiber to increase the oxygen-containing functional groups on the surface of the asphalt-based carbon fiber to obtain oxidized asphalt-based carbon fiber, and then uses a silane coupling agent to modify the oxidized asphalt-based carbon fiber to obtain a silane coupling agent modified carbon fiber, and then fixes nanosilver on the silane coupling agent modified carbon fiber to obtain nanosilver modified carbon fiber, and then fills the nanosilver modified carbon fiber into silicone to obtain a nanosilver modified carbon fiber@silicon thermal conductive composite material.

[0026] After the asphalt-based carbon fiber is surface-modified with silane coupling agent and nanosilver, the compatibility of the nanosilver-modified carbon fiber with the silicone matrix is ​​significantly improved. Compared with the asphalt-based carbon fiber, the contact angle between the nanosilver-modified carbon fiber and silicone is reduced by about 27°. The uncured silicone can spread better on the nanosilver-modified carbon fiber, overcoming the problem of poor compatibility between the prior art inorganic thermal conductive filler and the polymer matrix.

[0027] In addition, after modification, in the nanosilver-modified carbon fiber@organic silicon thermal conductive composite material obtained by the method of the present invention, the thermal conductivity of the nanosilver-modified carbon fiber@organic silicon thermal conductive composite material is 2.7 times that of pure silicone material and 1.3 times that of asphalt-based carbon fiber@organic silicon thermal conductive composite material at a lower filling amount of nanosilver. Moreover, after the nanosilver-modified carbon fiber is filled into silicone, the nanosilver-modified carbon fiber@organic silicon thermal conductive composite material has excellent mechanical properties and still has very good softness, and is suitable for use as a thermal conductive interface material.

[0028] 2. The nano-silver modified carbon fiber@organic silicon thermal conductive composite material obtained by the present invention can have high thermal conductivity and excellent mechanical properties under the premise of low filler filling amount.

[0029] 3. The present invention uses surface modification technology to modify the surface of asphalt-based carbon fiber with high thermal conductivity, improves the compatibility of asphalt-based carbon fiber in the silicone matrix, and reduces the interfacial thermal resistance of nanosilver-modified carbon fiber@silicon thermal conductive composite material. There are two reasons for reducing the interfacial thermal resistance. On the one hand, the compatibility of nanosilver-modified carbon fiber and silicone matrix is ​​improved, and the interfacial thermal resistance of nanosilver-modified carbon fiber and silicone matrix is ​​reduced; on the other hand, nanosilver modification reduces the interfacial thermal resistance between nanosilver-modified carbon fiber and forms a more complete thermal conductive path. Thereby, the thermal conductivity of nanosilver-modified carbon fiber@silicon thermal conductive composite material is greatly improved at a low filler filling amount. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a comparison chart of thermal conductivity of the nanosilver modified carbon fiber@organic silicon thermal conductive composite materials of Examples 1 to 3, the silicone sample of Comparative Example 1, and the asphalt-based carbon fiber@organic silicon thermal conductive composite material of Comparative Example 2.

[0031] Figure 2 These are thermogravimetric analysis graphs of the nanosilver modified carbon fiber@organic silicon thermal conductive composite materials of Examples 1 to 3, the silicone sample of Comparative Example 1, and the asphalt-based carbon fiber@organic silicon thermal conductive composite material of Comparative Example 2.

[0032] Figure 3 This is a comparison chart of the tensile strength of the nanosilver modified carbon fiber@organic silicon thermal conductive composite materials of Examples 1 to 3, the silicone sample of Comparative Example 1, and the asphalt-based carbon fiber@organic silicon thermal conductive composite material of Comparative Example 2.

[0033] Figure 4 This is a comparison chart of the elastic modulus of the nanosilver modified carbon fiber@organic silicon thermal conductive composite materials of Examples 1 to 3, the silicone sample of Comparative Example 1, and the asphalt-based carbon fiber@organic silicon thermal conductive composite material of Comparative Example 2.

[0034] Figure 5 This is a comparison chart of the elongation at break of the nanosilver modified carbon fiber@organic silicon thermal conductive composite materials of Examples 1 to 3, the silicone sample of Comparative Example 1, and the asphalt-based carbon fiber@organic silicon thermal conductive composite material of Comparative Example 2.

[0035] Figure 6 This is a hardness comparison chart of the nanosilver modified carbon fiber@organic silicon thermal conductive composite materials of Examples 1 to 3, the silicone sample of Comparative Example 1, and the asphalt-based carbon fiber@organic silicon thermal conductive composite material of Comparative Example 2.

[0036] Figure 7This is a comparison chart of the volume resistivity of the nanosilver modified carbon fiber@organic silicon thermal conductive composite materials of Examples 1 to 3, the silicone sample of Comparative Example 1, and the asphalt-based carbon fiber@organic silicon thermal conductive composite material of Comparative Example 2.

[0037] Figure 8 These are optical photographs of the compression and bending of the nanosilver modified carbon fiber@organic silicon thermal conductive composite material of Example 2 and the silicone sample of Comparative Example 1.

[0038] Fig. 9 The contact angle comparison diagram of the nano-silver modified carbon fiber and the nano-silver modified carbon fiber of Example 1 and organic silicon. DETAILED DESCRIPTION

[0039] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.

[0040] The nano-silver modified carbon fiber@organic silicon thermal conductive composite material of the present invention is prepared according to the following steps:

[0041] S1. Clean the asphalt-based carbon fiber, disperse the asphalt-based carbon fiber in acetone, reflux under normal pressure at 40-60°C for 10-14h, filter under reduced pressure, rinse with acetone, and dry in a vacuum drying oven at 50°C for 8h to obtain treated asphalt-based carbon fiber.

[0042] The treated asphalt-based carbon fiber is oxidized to increase the oxygen-containing functional groups on the surface of the treated asphalt-based carbon fiber to facilitate the reaction with the silane coupling agent. It is added to a binary mixed acid solution of concentrated sulfuric acid and concentrated nitric acid, reacted at 40-60°C for 8-12 hours, diluted with a large amount of deionized water, and filtered under reduced pressure. A large amount of deionized water is used for washing during the filtration process until the filtrate is neutral. After filtration, it is placed in a vacuum drying oven at 50°C for 8 hours to obtain oxidized asphalt-based carbon fiber.

[0043] S2. Add the oxidized asphalt-based carbon fiber of step S1 to an ethanol solution, use magnetic stirring to evenly disperse the oxidized asphalt-based carbon fiber in the ethanol solution, then add a silane coupling agent, reflux at 60-80°C under normal pressure for 6-8h, and then perform a reduced pressure filtration treatment. During the filtration process, rinse with a large amount of anhydrous ethanol, and after filtration, place in a vacuum drying oven at 50°C for 8h to obtain a silane coupling agent modified carbon fiber.

[0044] The volume ratio of the mass of the oxidized asphalt-based carbon fiber to the ethanol solution is 4-5 g: 20-30 mL.

[0045] The mass ratio of the oxidized asphalt-based carbon fiber to the silane coupling agent is 8-10:0.1-0.5.

[0046] The ethanol solution consists of anhydrous ethanol and deionized water in a volume ratio of 3-9:1.

[0047] S3. Disperse the silane coupling agent modified carbon fiber of step S2 in deionized water, add sodium citrate thereto and stir magnetically for 1 hour to obtain a silane coupling agent modified carbon fiber aqueous solution, then add silver nitrate solution and sodium borohydride solution dropwise to the silane coupling agent modified carbon fiber aqueous solution at 40-60°C, continue to react for 2-4 hours, and then perform reduced pressure filtration treatment, rinse with a large amount of deionized water during the filtration process, and place in a 50°C vacuum drying oven for 8 hours after filtration to obtain nanosilver modified carbon fiber.

[0048] Wherein, the mass ratio of silane coupling agent modified carbon fiber, sodium citrate, silver nitrate and sodium borohydride is 3-7g: 0.5-1.5g: 5.1-11.9mg: 3.192-3.99mg.

[0049] S4, the vinyl silicone oil, hydrogen silicone oil and Custer catalyst are mixed evenly to obtain a mixture, the nanosilver modified carbon fiber of step S3 is added to the mixture, and the mixture is stirred and homogenized at 12000rpm by a high-speed homogenizer for 3-5min, and then degassed in a vacuum drying oven at 40°C for 15-30min, and then vacuum cured at 100-140°C for 1-3h to obtain the nanosilver modified carbon fiber@silicon thermal conductive composite material.

[0050] The mass ratio of vinyl silicone oil, hydrogen-containing silicone oil and Castel catalyst is 80-100:2-4:0.3-0.7.

[0051] The mass ratio of the mixed material to the nano-silver modified carbon fiber is 100:15-25.

[0052] The technical solution of the present invention is further explained by using embodiments and comparative examples, as shown below:

[0053] Example 1

[0054] The preparation method of nano silver modified carbon fiber@organic silicon thermal conductive composite material comprises the following steps:

[0055] S1. Disperse 8 g of asphalt-based carbon fiber in 60 mL of acetone, reflux at normal pressure at 40°C for 10 h, filter under reduced pressure, rinse with acetone, and then dry in a vacuum drying oven at 50°C for 8 h to obtain treated asphalt-based carbon fiber.

[0056] The treated asphalt-based carbon fiber was added to a binary mixed acid solution of 98% concentrated sulfuric acid and 38% concentrated nitric acid in a volume ratio of 3:1. After reacting at 40°C for 8 hours, it was diluted with deionized water and filtered under reduced pressure. Deionized water was used for washing during the filtration process until the filtrate was neutral. After filtration, it was placed in a vacuum drying oven at 50°C for 8 hours to obtain oxidized asphalt-based carbon fiber.

[0057] S2. Add 8 g of the oxidized asphalt-based carbon fiber of step S1 into 40 mL of ethanol solution, stir magnetically for 1 hour to evenly disperse the oxidized asphalt-based carbon fiber in the ethanol solution, then add 0.1 g of 3-glycidyloxypropyltrimethoxysilane to the ethanol solution, reflux at 60°C for 6 hours, and then perform reduced pressure filtration. Rinse with anhydrous ethanol during the filtration process, and dry in a vacuum drying oven at 50°C for 8 hours after filtration to obtain silane coupling agent modified carbon fiber; wherein the ethanol solution is prepared in a ratio of 3:1 by volume of ethanol to deionized water.

[0058] S3. Take 3g of the silane coupling agent modified carbon fiber in step S2 and disperse it in 30mL of deionized water, then add 5mL of 0.1g / mL sodium citrate thereto, and stir magnetically for 1h to obtain an aqueous solution of the silane coupling agent modified carbon fiber; at 40°C, add silver nitrate solution and sodium borohydride solution dropwise to the aqueous solution of the silane coupling agent modified carbon fiber in a volume ratio of 1:1.2, continue to react for 2h, and then perform reduced pressure filtration. Rinse with deionized water during the filtration process, and after filtration, place in a vacuum drying oven at 50°C and dry for 8h to obtain nanosilver modified carbon fiber; wherein the amount of silver nitrate solution is 3mL, 1.7mg / mL, and the amount of sodium borohydride solution is 3.6mL, 0.38mg / mL.

[0059] S4. After 80 g of vinyl silicone oil, 2 g of hydrogenated silicone oil and 0.3 g of Custer catalyst are uniformly mixed, the nanosilver modified carbon fiber obtained in step S3 is added at a mass percentage of 15 wt%, and stirred and homogenized at 12000 rpm for 3 min using a high-speed homogenizer, followed by degassing in a vacuum drying oven at 40°C for 15 min, and then vacuum curing at 100°C for 3 h to obtain a nanosilver modified carbon fiber @ silicone thermal conductive composite material.

[0060] Example 2

[0061] The preparation method of the nano-silver modified carbon fiber@organic silicon thermal conductive composite material is the same as the preparation steps of Example 1, except that the mass percentage of the nano-silver modified carbon fiber is replaced from 15wt% to 20wt%.

[0062] Example 3

[0063] The preparation method of the nano-silver modified carbon fiber@organic silicon thermal conductive composite material is the same as the preparation steps of Example 1, except that the mass percentage of the nano-silver modified carbon fiber is replaced from 15wt% to 25wt%.

[0064] Example 4

[0065] The preparation method of nano silver modified carbon fiber@organic silicon thermal conductive composite material comprises the following steps:

[0066] S1. Disperse 10 g of asphalt-based carbon fiber in 70 mL of acetone, reflux at 50°C for 12 hours, filter under reduced pressure, rinse with acetone, and dry in a vacuum drying oven at 50°C for 8 hours to obtain treated asphalt-based carbon fiber.

[0067] The treated asphalt-based carbon fiber was added to a binary mixed acid solution of 98% concentrated sulfuric acid and 38% concentrated nitric acid in a volume ratio of 3.5:1, reacted at 50°C for 10 hours, diluted with deionized water, and filtered under reduced pressure. Deionized water was used for washing during the filtration process until the filtrate was neutral. After filtration, it was placed in a vacuum drying oven at 50°C for 8 hours to obtain oxidized asphalt-based carbon fiber.

[0068] S2. Add 9 g of the oxidized asphalt-based carbon fiber of step S1 into 50 mL of ethanol solution, stir magnetically for 1 hour to evenly disperse the oxidized asphalt-based carbon fiber in the ethanol solution, then add 0.3 g of 3-glycidyloxypropyltrimethoxysilane to the ethanol solution, reflux under normal pressure at 70°C for 7 hours, and then perform reduced pressure filtration. Rinse with anhydrous ethanol during the filtration process, and dry in a vacuum drying oven at 50°C for 8 hours after filtration to obtain silane coupling agent modified carbon fiber; wherein the ethanol solution is prepared in a ratio of 6:1 by volume of ethanol to deionized water.

[0069] S3. Take 5 g of the silane coupling agent modified carbon fiber in step S2 and disperse it in 40 mL of deionized water, then add 5 mL of 0.2 g / mL sodium citrate thereto, and stir magnetically for 1 hour to obtain a silane coupling agent modified carbon fiber aqueous solution; at 50°C, add silver nitrate solution and sodium borohydride solution dropwise to the silane coupling agent modified carbon fiber aqueous solution in a volume ratio of 1:1.3, continue to react for 3 hours, and then perform reduced pressure filtration. Rinse with deionized water during the filtration process, and after filtration, place in a 50°C vacuum drying oven and dry for 8 hours to obtain nanosilver modified carbon fiber; wherein the amount of silver nitrate solution is 5 mL, 1.7 mg / mL, and the amount of sodium borohydride solution is 6.5 mL, 0.38 mg / mL.

[0070] S4. After 90 g of vinyl silicone oil, 3 g of hydrogenated silicone oil and 0.5 g of Custer catalyst are uniformly mixed, the nanosilver modified carbon fiber obtained in step S3 is added at a mass percentage of 20 wt%, and stirred and homogenized at 12000 rpm for 4 min using a high-speed homogenizer, followed by degassing in a 40°C vacuum drying oven for 20 min, and then vacuum curing at 120°C for 2 h to obtain a nanosilver modified carbon fiber @ silicone thermal conductive composite material.

[0071] Example 5

[0072] The preparation method of nano silver modified carbon fiber@organic silicon thermal conductive composite material comprises the following steps:

[0073] S1. Disperse 15 g of asphalt-based carbon fiber in 80 mL of acetone, reflux at normal pressure at 60°C for 14 h, filter under reduced pressure, rinse with acetone, and then dry in a vacuum drying oven at 50°C for 8 h to obtain treated asphalt-based carbon fiber.

[0074] The treated asphalt-based carbon fiber was added to a binary mixed acid solution of 98% concentrated sulfuric acid and 38% concentrated nitric acid in a volume ratio of 4:1. After reacting at 60°C for 12 hours, it was diluted with deionized water and filtered under reduced pressure. Deionized water was used for washing during the filtration process until the filtrate was neutral. After filtration, it was placed in a vacuum drying oven at 50°C for 8 hours to obtain oxidized asphalt-based carbon fiber.

[0075] S2. Add 10 g of the oxidized asphalt-based carbon fiber of step S1 into 60 mL of ethanol solution, stir magnetically for 1 hour to evenly disperse the oxidized asphalt-based carbon fiber in the ethanol solution, then add 0.5 g of 3-glycidyloxypropyltrimethoxysilane to the ethanol solution, reflux at 80°C for 8 hours, and then perform reduced pressure filtration. Rinse with anhydrous ethanol during the filtration process, and dry in a vacuum drying oven at 50°C for 8 hours after filtration to obtain silane coupling agent modified carbon fiber; wherein the ethanol solution is prepared in a volume ratio of ethanol to deionized water of 9:1.

[0076] S3. Take 7g of the silane coupling agent modified carbon fiber in step S2 and disperse it in 50mL of deionized water, then add 5mL of 0.3g / mL sodium citrate thereto, and stir magnetically for 1h to obtain a silane coupling agent modified carbon fiber aqueous solution; at 60°C, add silver nitrate solution and sodium borohydride solution dropwise to the silane coupling agent modified carbon fiber aqueous solution in a volume ratio of 1:1.5, continue to react for 4h, and then perform reduced pressure filtration. Rinse with deionized water during the filtration process, and after filtration, place in a 50°C vacuum drying oven and dry for 8h to obtain nanosilver modified carbon fiber; wherein the amount of silver nitrate solution is 7mL, 1.7mg / mL, and the amount of sodium borohydride solution is 8.5mL, 0.38mg / mL.

[0077] S4. After 100 g of vinyl silicone oil, 4 g of hydrogenated silicone oil and 0.7 g of Custer catalyst are uniformly mixed, the nanosilver modified carbon fiber obtained in step S3 is added at a mass percentage of 25 wt%, and stirred and homogenized at 12000 rpm for 5 min using a high-speed homogenizer, followed by degassing in a vacuum drying oven at 40°C for 30 min, and then vacuum curing at 140°C for 1 h to obtain a nanosilver modified carbon fiber@silicone thermal conductive composite material.

[0078] Comparative Example 1

[0079] The preparation method of organosilicon comprises the following steps:

[0080] 100 g of vinyl silicone oil, 4 g of hydrogenated silicone oil and 0.7 g of Custer catalyst were mixed evenly, stirred and homogenized at 12000 rpm for 5 min using a high-speed homogenizer, then degassed in a vacuum drying oven at 40° C. for 30 min, and then vacuum cured at 140° C. for 1 h to obtain silicone.

[0081] Comparative Example 2

[0082] A method for preparing a pitch-based carbon fiber@organic silicon thermally conductive composite material comprises the following steps:

[0083] After mixing 100g of vinyl silicone oil, 4g of hydrogenated silicone oil and 0.7g of Castel catalyst evenly, add asphalt-based carbon fiber at a mass percentage of 20wt%, and stir and homogenize with a high-speed homogenizer at 12000rpm for 5min, then degas in a vacuum drying oven at 40℃ for 30min, and then vacuum cure at 140℃ for 1h to obtain an asphalt-based carbon fiber@silicone thermal conductive composite material.

[0084] The present invention's embodiments 1 to 5 all produce nano-silver modified carbon fiber @ organic silicon thermal conductive composite materials with low thermal conductive filler filling amount, high thermal conductivity, good thermal stability, and excellent mechanical properties. The nano-silver modified carbon fiber @ organic silicon thermal conductive composite materials of embodiments 1 to 3 are used as examples for research, and compared with comparative examples 1 to 2. The specific research methods and results are as follows:

[0085] In the following experiments, A is the pure silicone sample of Comparative Example 1; B is the nanosilver modified carbon fiber @ silicone thermal conductive composite material sample of Example 1, C is the nanosilver modified carbon fiber @ silicone thermal conductive composite material sample of Example 2, D is the nanosilver modified carbon fiber @ silicone thermal conductive composite material sample of Example 3, and E is the asphalt-based carbon fiber @ silicone thermal conductive composite material sample of Comparative Example 2.

[0086] 1. Thermal conductivity test of nano-silver modified carbon fiber@organic silicon thermal conductive composite material:

[0087] The thermal conductivity of the five samples A, B, C, D, and E was tested using the LongGwin9389 thermal resistance tester from Shanghai Longwin. The five samples A, B, C, D, and E were cut into square samples of 30mm×30mm and 1mm, 1.5mm, and 2mm thick, respectively. The thermal resistance of the five samples A, B, C, D, and E at different thicknesses was measured, and the thermal conductivity of each sample was calculated based on the thermal resistance and thickness of the sample. The results are shown in the figure. Figure 1 shown.

[0088] Figure 1 The results show that the thermal conductivity of sample C is 1.406 W·m -1 ·K -1 , which is 2.7 times the thermal conductivity of sample A and 1.3 times the thermal conductivity of sample E. This is mainly because the nanosilver-modified carbon fiber obtained after modification with silane coupling agent and nanosilver has better compatibility with the silicone matrix, and the thermal conductivity network between filler and matrix and filler and filler is more perfect, thus showing better thermal conductivity. The thermal conductivity of sample C is significantly higher than that of sample E, which shows that under the condition that the filling amount of asphalt-based carbon fiber and nanosilver-modified carbon fiber is equal, the nanosilver-modified carbon fiber modified by silane coupling agent and nanosilver can improve the thermal conductivity of silicone more significantly. The thermal conductivity of sample C is higher than that of sample B and sample D, which shows that the amount of nanosilver-modified carbon fiber has a significant effect on the thermal conductivity of nanosilver-modified carbon fiber@silicon thermal conductive composite material, and it needs to be maintained at an appropriate level to achieve the high thermal conductivity of nanosilver-modified carbon fiber@silicon thermal conductive composite material.

[0089] 2. Thermal stability test of nano-silver modified carbon fiber@organic silicon thermal conductive composite material:

[0090] Thermogravimetric analysis of five samples A, B, C, D, and E was performed using a German NETZSCH thermogravimetric analyzer (TG209F3Tarsus) to evaluate the thermal stability of the nanosilver modified carbon fiber@organic silicon thermal conductive composite material. The five samples A, B, C, D, and E were cut into small cubes with a side length of 2 mm, placed in the crucible of the thermogravimetric analyzer, and tested under nitrogen atmosphere protection, with a heating rate of 10°C / min and a test temperature range of 30-800°C. The sample mass and temperature curve were obtained based on the thermogravimetric analysis, and the thermal stability of the samples was analyzed and evaluated. The results are shown in Figure 2. Figure 2 shown.

[0091] Figure 2The results show that for sample A, the starting temperature of weight loss is 394.1℃, the ending temperature is 560.9℃, the final mass change is 96.27%, and sample A is basically completely decomposed. For samples B, C, and D, the starting temperature of weight loss of nanosilver-modified carbon fiber @ silicone thermal conductive composite material is basically around 520℃, and the ending temperature is around 640℃, which is significantly higher than the weight loss temperature of sample A. The starting temperature of weight loss of sample C is 523.0℃, and the ending temperature is 644.1℃. Compared with sample A, the thermal stability is greatly improved, and it has better heat resistance. From the whole weight loss process of sample C and sample E, the thermal stability of sample C is slightly higher than that of sample E, but the difference in thermal stability between the two is not very obvious. The addition of nanosilver-modified carbon fiber significantly improves the thermal stability of nanosilver-modified carbon fiber @ silicone thermal conductive composite material, which can ensure the better service performance of nanosilver-modified carbon fiber @ silicone thermal conductive composite material as a thermal conductive interface material.

[0092] 3. Mechanical properties test of nano-silver modified carbon fiber@organic silicon thermal conductive composite material:

[0093] The mechanical properties of the five samples A, B, C, D, and E were tested by an electronic universal tensile testing machine. First, according to the national standard GB / T1040-2018, the five samples A, B, C, D, and E were stretched into dumbbell-shaped specimens with a gauge length of 20 mm, an aspect ratio of 5:1, and a thickness of about 2 mm. Before the test, the thickness of the specimen was accurately measured with a vernier caliper, and then the test was carried out at a tensile rate of 10 mm / min. Each specimen was tested 5 times in parallel, and the tensile strength, elastic modulus, and elongation at break of the sample were characterized based on the average value of the test results. The results are shown in the figure. Figure 3-Figure 5 shown.

[0094] Figure 3 The results show that the tensile strength of sample A is 0.063MPa, and the tensile strength of sample C is 0.168MPa. Compared with sample A, the tensile strength of sample C is more than twice that of sample A. Moreover, under the condition that the filling amount of asphalt-based carbon fiber and nanosilver-modified carbon fiber is equal, the tensile strength of sample C is slightly higher than that of sample E, which may be caused by the modification of asphalt-based carbon fiber. With the increase of the filling amount of nanosilver-modified carbon fiber, the tensile strength of sample A, sample B, sample C, and sample D gradually increases. This is mainly because the addition of silane coupling agent and nanosilver-modified carbon fiber enhances the mechanical properties of nanosilver-modified carbon fiber@organic silicon thermal conductive composite materials.

[0095] Figure 4The results show that the elastic modulus of sample A is 0.102MPa, and the tensile strength of sample C is 0.225MPa. Compared with sample A, the elastic modulus of sample C is more than twice as high, and under the condition that the filling amount of asphalt-based carbon fiber and nanosilver-modified carbon fiber is equal, the elastic modulus of sample C is slightly higher than that of sample E. With the increase of the filling amount of nanosilver-modified carbon fiber, the elastic modulus of sample A, sample B, sample C, and sample D gradually increases, showing the same change trend as the tensile strength of the sample.

[0096] Figure 5 The results show that the elongation at break of sample A is 73.4%, the elongation at break of samples C and D are 155% and 160% respectively, and under the condition of equal filling amount of asphalt-based carbon fiber and nano-silver modified carbon fiber, the elongation at break of sample C is higher than that of sample E. The elongation at break of samples A, B, C and D also shows an increasing trend with the increase of carbon fiber, and at a higher carbon fiber filling amount, the nano-silver modified carbon fiber@organic silicon thermal conductive composite material has better flexibility and can meet the mechanical property requirements of thermal conductive materials.

[0097] 4. Shore hardness test of nano-silver modified carbon fiber@organic silicon thermal conductive composite material:

[0098] The Shore hardness of the five samples A, B, C, D, and E was measured using an O-type rubber hardness tester from Taizhou AiCe Instrument Co., Ltd. During the test, the five samples A, B, C, D, and E to be tested were first placed on a solid horizontal surface. The hardness tester was held vertically by hand so that the hardness tester needle was at least 12 mm away from the edge of the sample, and the hardness tester needle was vertically pressed into the sample to be tested. When the hardness tester foot and the sample were in full contact, the hardness value was read within 1 second. The hardness value was tested five times at different locations at least 6 mm apart from each other and the average value was calculated. The results are as follows: Figure 6 shown.

[0099] Figure 6 The results show that the Shore hardness of the four samples A, B, C, and D all show an increasing trend with the increase of the nanosilver modified carbon fiber filling amount. This is mainly because the high-hardness nanosilver modified carbon fiber is evenly distributed in the silicone matrix, thereby enhancing the overall hardness of the nanosilver modified carbon fiber@silicon thermal conductive composite material. Under the condition that the filling amount of asphalt-based carbon fiber and nanosilver modified carbon fiber is equal, the Shore hardness of sample C is slightly higher than that of sample E, which may be caused by the surface modification of nanosilver on the carbon fiber. The Shore hardness of sample C is 51.0H00. Compared with sample A, the Shore hardness of sample C is increased by about 34%. Sample C can withstand appropriate external pressure in the application environment.

[0100] 5. Volume resistivity test of nano-silver modified carbon fiber@organic silicon thermal conductive composite material:

[0101] The resistance of the five samples A, B, C, D, and E was measured using the iviumstst.h electrochemical workstation of the Dutch ivium company, and the volume resistivity of each sample was calculated. First, the five samples A, B, C, D, and E were cut into rectangular samples with a specification of 10mm×10mm×2mm. During the test, the samples were placed between two sensors on the electrochemical workstation and tested using the transient DC impedance method. The test temperature was 25°C. The volume resistivity of each sample was calculated based on the resistance value obtained from the test. The results are shown in the figure. Figure 7 shown.

[0102] Figure 7 The results show that the volume resistivity of sample A is 9.42×10 12 Ω·cm. With the increase of the filling amount of nanosilver modified carbon fiber, the volume resistivity of the four samples A, B, C, and D showed a decreasing trend. Under the condition that the filling amount of asphalt-based carbon fiber and nanosilver modified carbon fiber is equal, the volume resistivity of sample C is 9.96×10 11 Ω·cm, slightly higher than the volume resistivity of sample E (1.013×10 12 Ω·cm). In addition, the volume resistivity of samples A, B, C, D, and E is higher than 10 9 Ω·cm, which can meet the use requirements of electronic packaging materials for electrical insulation.

[0103] In the present invention, after comparison with Examples 1-3, it is found that in Example 2, when the mass percentage of nanosilver modified carbon fiber is 20%, the comprehensive performance is best. Based on this consideration, a comparative experiment is carried out with the mass percentage of asphalt-based carbon fiber being 20% ​​as a control, that is, Comparative Example 2 is used as the control group; although the performance of Examples 1 and 3 is not as good as Comparative Example 2, under the condition of the same doping amount of asphalt-based carbon fiber and nanosilver modified carbon fiber, that is, the doping amount is 15% or 25%, the performance of Examples 1 and 3 is better.

[0104] Figure 8 The optical photographs of the compression and bending of the nanosilver-modified carbon fiber@organic silicon thermal conductive composite material of Example 2 and the silicone sample of Comparative Example 1. Both sample A and sample C can be bent repeatedly by 180° without affecting the tensile strength and hardness, which indicates that the nanosilver-modified carbon fiber@organic silicon thermal conductive composite material has excellent flexibility.

[0105] Fig. 9The contact angles of the nanosilver-modified carbon fiber and the asphalt-based carbon fiber on the silicone surface of Example 1 are compared. The results show that, compared with the asphalt-based carbon fiber, the contact angle of the nanosilver-modified carbon fiber and the silicone is reduced by about 27°, and the uncured silicone can spread better on the nanosilver-modified carbon fiber. The compatibility of the nanosilver-modified carbon fiber with the uncured silicone is significantly better than that of the asphalt-based carbon fiber.

[0106] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a nano-silver modified carbon fiber@organic silicon thermal conductive composite material, characterized in that: The steps include: The asphalt-based carbon fiber is subjected to oxidation treatment to increase the oxygen-containing functional groups on the surface of the asphalt-based carbon fiber to obtain oxidized asphalt-based carbon fiber; The oxidized asphalt-based carbon fiber is modified by using a silane coupling agent to obtain a silane coupling agent-modified carbon fiber; The silane coupling agent modified carbon fiber is mixed with a sodium citrate solution to obtain a silane coupling agent modified carbon fiber aqueous solution, the silane coupling agent modified carbon fiber aqueous solution, a silver nitrate solution and a sodium borohydride solution are mixed, and a silver ion reduction reaction is performed, sodium citrate is used as a stabilizer to prevent nanosilver from agglomerating, and then water is removed to obtain nanosilver modified carbon fiber; Vinyl silicone oil, hydrogen-containing silicone oil and Castel catalyst are mixed to obtain a mixture, nanosilver modified carbon fiber is added to the mixture, and the mixture is first homogenized and then vacuum cured. During the curing process, under the action of the catalyst, the vinyl silicone oil and the hydrogen-containing silicone oil undergo a silylation reaction and cross-linking to obtain a nanosilver modified carbon fiber@silicone thermal conductive composite material.

2. The method for preparing the nano-silver modified carbon fiber@organic silicon thermally conductive composite material according to claim 1, characterized in that: The mass ratio of the silane coupling agent modified carbon fiber, sodium citrate, silver nitrate and sodium borohydride is 3-7g: 0.5-1.5g: 5.1-11.9mg: 3.192-3.99mg.

3. The method for preparing the nano-silver modified carbon fiber@organic silicon thermal conductive composite material according to claim 1, characterized in that: The method of silver ion reduction reaction is: stirring the reaction at 40-60° C. for 2-4 hours.

4. The method for preparing the nano-silver modified carbon fiber@organic silicon thermal conductive composite material according to claim 1, characterized in that: The mass ratio of vinyl silicone oil, hydrogen-containing silicone oil and Custer catalyst is 80-100:2-4:0.3-0.

7.

5. The method for preparing the nano-silver modified carbon fiber@organic silicon thermal conductive composite material according to claim 1, characterized in that: The mass ratio of the mixed material to the nano-silver modified carbon fiber is 100:15-25.

6. The method for preparing the nano-silver modified carbon fiber@organic silicon thermal conductive composite material according to claim 1, characterized in that: The oxidation treatment method is: prepare a mixed acid solution containing sulfuric acid and nitric acid, place the asphalt-based carbon fiber in the mixed acid solution, and perform oxidation reaction at 40-60° C. for 8-12 hours; Among them, the volume fraction of sulfuric acid is 98%, the volume fraction of nitric acid is 38%, and the volume ratio of sulfuric acid to nitric acid is 3-4:

1.

7. The method for preparing the nano-silver modified carbon fiber@organic silicon thermal conductive composite material according to claim 1, characterized in that: The modification method is: mixing the oxidized asphalt-based carbon fiber and the silane coupling agent in an ethanol solution, and then refluxing at 60-80° C. under normal pressure for 6-8 hours.

8. The method for preparing the nano-silver modified carbon fiber@organic silicon thermal conductive composite material according to claim 1, characterized in that: The curing operation is: vacuum curing at 100-140°C for 1-3h.

9. A nano-silver modified carbon fiber@organic silicon thermal conductive composite material obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The diameter of the nano-silver modified carbon fiber is 3-10 μm and the length is 150-200 μm.

10. Use of the nano-silver modified carbon fiber@organic silicon thermal conductive composite material according to claim 9 in the preparation of a thermal conductive interface material.

Citation Information

Cited By

  • Oriented carbon fiber filled organic silicon composite material as well as preparation method and application thereof

    CN119899534A